Knowledge, Attitudes and Practices of High School Students with Menarche in Parakou/Benin in 2014 - SIDI, Imorou Rachidi; SALIFOU, KABIBOU; OBOSSOU, Awadé Afoukou Achille; HOUNKPATIN, BENJAMIN IGNACE BODOUNRIN; HOUNKPONOU-AHOUIGNAN, Fanny; PERRIN, RENÉ-XAVIER (My University, 2016)
Objective: Assess the knowledge level, attitudes and practices of high school students confronted with menarche in Parakou in 2014. Methods: This study was descriptive and cross-sectional. It was carried out from June 1 to September, 2014. A self-administered questionnaire permitted to collect information. Results: Upon the appearance of menarche, the mean age was 13.72 ± 1.37 years, Menarche was known by 60.72% of the respondents before it occurs. The main source of information about menarche was mother in 57.75% of the cases. For 90% of them, mother was the preferred source of information about this issue. Fear and anxiety were the feeling that inspired 72.55% of the respondents on the appearance of first menstruation. Towels made with folded fabrics were used by 89.78% of the adolescents and their main fears were menstrual bleeding which may stain their uniforms, and strong odors emanating from that type of towel. During the survey, 61% of the 1,100 girls already had sex for the first time. Upon first sexual intercourse in respondents, the mean age was 16.34 ± 1.84 years. Conclusion: Parakou high school students’ knowledge about menarche and its effects in terms of reproduction and sexuality is insufficient. This explains why they feel anxious when they get their first periods. This also justifies tendency towards ill-prepared sexuality.
Keywords: Menarche; High school students; Knowledge; Attitudes; Practices